Engagement and tennis: The applicability of occupational psychology to the world of sport - Scamardella, F.; Casillo, V.; Cusano, P. (Journal of Human Sport & Exercise, 2020)
The working activity, as well as the sports one, foresees that results have to be achieved and be decided/evaluated by others, a personal physical and mental effort is required in a well-defined time and space, constraints and limitations established by the nature of the tasks have to be overcome, and a consistent and defined part of one's own time has to be employed. The aim of this research is to demonstrate how work phenomena (specifically work engagement) can be conveyed to the world of sport, highlighting the applicability of occupational psychology also in a sports context.